Biohydrogen production by dark fermentation of acid hydrolyzed sago wastewater using enterobacter aerogenes - Ulhiza, Tami Astie (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
As the global fuel hike is inevitable, it is essential to find other options which can substitute fossil fuel. Hydrogen appears as the promising energy alternative which not only meets the demand of energy but also results in the clean environment. However, the current production of hydrogen is releasing much energy and pollution. Therefore, biological approach to produce hydrogen by using microorganism and waste becomes prominent. In the development of biohydrogen research, there is still limited number of records on utilizing sago wastewater as a source of energy. Thus, the main aim of this study is to produce biohydrogen from sago wastewater using Enterobacter aerogenes (E. aerogenes). In this lab scale study, several sequential methods were used in evaluating the optimization process which was included in the research objectives. Firstly, 10 physico-chemical factors (sago wastewater concentration, temperature, pH, inoculum size, malt extract, yeast extract, iron, magnesium, copper, and nitrogen sparging) affecting biohydrogen production was selected in the Plackett-Burman design. Secondly, the factors were optimized using OFAT method followed by FCCCD under RSM. Thirdly, the kinetics parameters of E. aerogenes cell growth, substrate uptake, and biohydrogen production were determined. It was found that early screening using Plackett-Burman design, yeast extract (positive effect), temperature (negative effect) and inoculum size (negative effect) had the most profound effect to the biohydrogen production. The three factors were then subjected to OFAT to find the possible optimum range. It was discovered from OFAT that the inoculum size was already at the optimum condition at 5%. Meanwhile, the possible optimum range for yeast extract concentration and temperature were nearly at 3 g/L and 30ºC, respectively, which were then applied as the middle points in the RSM. A total of 11 runs were generated in RSM. The highest hydrogen production was obtained from Run 7 (hydrogen concentration and yield were 629.80 µmol/L and 12.13 mmol H2/mol glucose, respectively). The statistical analysis of ANOVA revealed that the linear and quadratic term of yeast extract as well as the quadratic term of temperature were indeed significant to the biohydrogen production. After the whole optimization processes, the maximum hydrogen concentration and yield were recorded to be 630.67 µmol/L and 7.42 mmol H2/mol glucose, respectively, which were obtained under the optimum condition (inoculum size 5%, yeast extract concentration 4.8 g/L, and temperature 31ºC). The kinetic study was then conducted under the optimum condition using 1 L of Schott bottle. It was found that the exponential phase of E. aerogenes along with biohydrogen production occurred between the 9th and 30th hour of fermentation period. It was then concluded that biohydrogen produced by E. aerogenes is a growth-associated product. Several kinetic parameters that were successfully derived from Monod model were Yxs (0.87 g/g), Yps (0.003 mol/mol), Ypx (0.029 g/g), µ (0.12 h-1), td (6 h) and qp (0.0035 hour-1). Moreover, a cumulative hydrogen production curve fitted by the modified Gompertz equation suggested that Hmax, Rmax, and λ from this study were 15.10 mL, 2.18 mL/h, and 9.84 h, respectively. Although biohydrogen was successfully produced from sago wastewater, the improvement of the yield for further investigation is still needed due to the limitations of this study, especially on improvement of the strain, pre-treatment method of the waste, effect of the by-products, and scale up process.